4x-6-2x=4

Simple and best practice solution for 4x-6-2x=4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-6-2x=4 equation:


Simplifying
4x + -6 + -2x = 4

Reorder the terms:
-6 + 4x + -2x = 4

Combine like terms: 4x + -2x = 2x
-6 + 2x = 4

Solving
-6 + 2x = 4

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 2x = 4 + 6

Combine like terms: -6 + 6 = 0
0 + 2x = 4 + 6
2x = 4 + 6

Combine like terms: 4 + 6 = 10
2x = 10

Divide each side by '2'.
x = 5

Simplifying
x = 5

See similar equations:

| Q-1/21/2 | | -5+2m=25 | | 5=n/2-5 | | 6+6d=54 | | 8x-9=143 | | z/3-1=1 | | 5x-4+6x-9-4=2+2x+7 | | -2+10n=78 | | 2x+3-7(x-1)=2(x-55)+5x | | 1/7f-5(1/5)=9/14 | | a/6-1=2 | | p/9=93=-84 | | 4f+18=-50 | | 8+2s=16 | | X^4-X^2+240=0 | | -3m+5=2 | | k/7-3=2 | | 16+24c=22.5 | | C(h)=200+59.95h | | -32+17x=17x | | -100x=7 | | 1/3y-2=-8 | | 8z+7=95 | | 3x-15=-16 | | -4(n+3)=-3(n+4) | | (2a^-2b^2/10ab)^-2 | | 6c^2-8c= | | f(x)=5-6x^2 | | fA(x)=5-6x^2 | | 2x-3y-6z= | | 53=17+6c | | -6q+8=-82 |

Equations solver categories